Loss and Gain in Translation of The Broken Ear Comic - Lutfiana, Dina; Jayantini, I Gusti Agung Sri Rwa; Pratiwi, Desak Putu Eka (Institut Pariwisata dan Bisnis Internasional, 2024)
This study aims to find out the kinds of translation techniques applied in the translation of The Broken Ear comic and how the loss and gain occur. The theory applied was Molina, and Albir's translation strategies (2002) and the concept of loss and gain from Nida’s was also applied in this study. The data of this study were taken from comic entitled The Broken Ear. In collecting the data, the researcher used the observation method by reading, taking note, and classifying the data based on the theories used. The method used in this research is descriptive qualitative. There are ten types of translation techniques within the highest number was modulation 21, 21% (7 data) and the linguistic compression 21,21% (7). Then, it is followed by amplification that takes 12,12% (4 data), borrowing takes 6,06% (2 data), literal translation takes 3,03% (1 data), calque takes 6,06% ( 2 data), discursive creation takes 6,06% (2), reduction takes 18,18% (6 data). The last lowest percentages occurred were particularization 3, 03% (1), and adaptation 3, 03% (1 data) techniques. Of 33 data in the form of comic, loss of information occurs in the highest percentage, that is 84, 84% (28 data) and the lowest was gain of information takes 15, 15% (5 data).